2012
DOI: 10.1007/s00253-012-4330-7
|View full text |Cite
|
Sign up to set email alerts
|

Soyfoods and soybean products: from traditional use to modern applications

Abstract: Soybean products (soyfoods), reported as potential functional foods, are implicated in several health-enhancing properties, such as easing the symptoms of postmenopausal women, reducing the risk of osteoporosis, preventing cardiovascular disease, and antimutagenic effects. Isoflavone, for example, is one of the most important compounds abundantly found in soybean, mainly accounting for the health-enhancing properties as mentioned earlier. However, most biological activities of isoflavones are mainly attributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
110
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(127 citation statements)
references
References 103 publications
1
110
0
1
Order By: Relevance
“…However, in many regions of Asia, Africa, and Europe, soybean is primarily grown for its highprotein content and as a food crop. In Asia, soybean is a traditional staple food in many countries, and both fermented and nonfermented soyfoods are a major source of protein and healthy bioactive compounds to the human diet (Chen et al, 2012). In Africa, soybean is still a minor and new crop continuously growing in acreage with 1.7 mio ha harvested in 2013, particularly in Nigeria and South Africa (FAOSTAT, 2015).…”
Section: Nutritional Composition Of Legume Cropsmentioning
confidence: 99%
“…However, in many regions of Asia, Africa, and Europe, soybean is primarily grown for its highprotein content and as a food crop. In Asia, soybean is a traditional staple food in many countries, and both fermented and nonfermented soyfoods are a major source of protein and healthy bioactive compounds to the human diet (Chen et al, 2012). In Africa, soybean is still a minor and new crop continuously growing in acreage with 1.7 mio ha harvested in 2013, particularly in Nigeria and South Africa (FAOSTAT, 2015).…”
Section: Nutritional Composition Of Legume Cropsmentioning
confidence: 99%
“…At present, soybean is increasingly utilized for human consumption in many countries world-wide, and a growing number of both traditional and modern soy food products is on the market because of favorable nutrition and health properties (Chen et al 2012;Xiao 2008). Therefore, soybean production has been extended to new growing regions with partly unknown soil characteristics and heavy metal status.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, evidence from studies has confirmed the carcinogenic effects of steroidal estrogens in the development of breast cancer, suggesting the feasibility of antiestrogen therapy in inhibiting tumor malignancy and growth [2,3]. Phytoestrogens, a class of plant-derived phenolic compounds, are structurally similar to mammalian estrogens, which determines their abilities to bind to estrogen receptors (ER)-α and ER-β and then mimic estrogen effects [4]. Nevertheless, epidemiologic studies reveal that there are fewer breast cancer cases in Asian women than Western women, partially owing to the higher consumption of phytoestrogens from soybean products in Asian countries [5].…”
Section: Introductionmentioning
confidence: 99%